2014
DOI: 10.1371/journal.pone.0111785
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics and Inflammation in Atherosclerotic Plaque Erosion and Plaque Rupture: Implications for Cardiovascular Events in Women

Abstract: ObjectiveAlthough plaque erosion causes approximately 40% of all coronary thrombi and disproportionally affects women more than men, its mechanism is not well understood. The role of tissue mechanics in plaque rupture and regulation of mechanosensitive inflammatory proteins is well established, but their role in plaque erosion is unknown. Given obvious differences in morphology between plaque erosion and rupture, we hypothesized that inflammation in general as well as the association between local mechanical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 37 publications
0
11
0
3
Order By: Relevance
“…Eruptive calcified nodules are the less common cause of thrombosis [5]. While recent analyses suggest different etiologies for plaque rupture and plaque erosion [5,9,10], mechanisms of plaque rupture have been extensively studied and morphological features of rupture-prone plaques are well established (Table 1) [8]. No single morphological features have been identified for erosion-prone plaques; nevertheless, we know that eroded plaques with thrombosis are rarely calcified or associated with expansive remodeling, and show minimal inflammation [8,11].…”
Section: High-risk Plaquementioning
confidence: 99%
See 1 more Smart Citation
“…Eruptive calcified nodules are the less common cause of thrombosis [5]. While recent analyses suggest different etiologies for plaque rupture and plaque erosion [5,9,10], mechanisms of plaque rupture have been extensively studied and morphological features of rupture-prone plaques are well established (Table 1) [8]. No single morphological features have been identified for erosion-prone plaques; nevertheless, we know that eroded plaques with thrombosis are rarely calcified or associated with expansive remodeling, and show minimal inflammation [8,11].…”
Section: High-risk Plaquementioning
confidence: 99%
“…In line with the experimental and autopsy studies, longitudinal and cross-sectional human coronary and carotid studies have shown an increase in plaque necrotic core, calcium [35], and strain [45], development of expansive remodeling [35,46], presence of IPH [47], large necrotic core [34,46,48], a necrotic core in contact with the lumen [48], and napkin-ring sign [46] in areas exposed to high WSS. Meanwhile, some data show that WSS might not have the same role in development of plaque erosion as it has in the development of plaque rupture [9,10]. …”
Section: High Wall Shear Stressmentioning
confidence: 99%
“…Autopsy studies suggest that markers of inflammation are significantly lower in plaque erosion compared with plaque rupture, with sparse infiltration of macrophages and T lymphocytes within the vessel wall . Other studies, however, have suggested an important role for neutrophil infiltrates at sites of plaque erosion .…”
Section: Introductionmentioning
confidence: 99%
“…В результате проведения морфологических исследований активированные макрофаги, тучные клетки и тканевой фактор в большом количестве обнаруживаются именно в области разрыва. Эрозия бляшки не связана так тесно, как разрыв, с активностью системного и местного воспаления и апоптоза [17]. Механизмы возникновения эрозии на поверхности бляшки менее изучены, но определенно в этом процессе имеют значение разрушение и перестройка внеклеточного матрикса.…”
unclassified